Future Trends for a First Course in Control Engineering - Rossiter, John Anthony (Frontiers in Control Engineering, 2022)
This review summarises recent thinking in the academic control community on the future of control as a topic and thus on the design and focus of control courses at university. It is notable that the current thinking is quite controversial and significantly at odds with traditional practice, and thus implementing such changes will require substantial effort and will from the community.